Religious Tradition and Technology: Debate among Penghulus about Online Marriage Law in Banjarmasin - Hayati, Siti Muna; Khitam, Husnul; Erfan, Zainul; Amini, Afifah (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
This article explores the perspectives of penghulus (marriage functionaries) in Banjarmasin regarding online marriage contracts, navigating the interplay between religious tradition and technological. Drawing upon differences in interpretation among Islamic jurists, the article elucidates varying views on the validation of marriage contracts, focusing on the concept of ittiḥād al-majlis (unity of session). This concept significantly shapes penghulus’ opinions on the legitimacy of online marriage contracts. Against this backdrop, the article analyses the factors driving discourse among penghulus regarding online marriage contracts and their implications within Banjarese community. Conducting interviews with 12 penghulus in Banjarmasin over a three-month period from September to November 2023, the study underscores the importance of religious tradition in Banjarmasin society and its adaptation to technological progress in interpreting Islamic law. The study finds that while the majority of penghulus oppose online marriage contracts, a minority endorse them under specific conditions. Those against them argue that ittiḥād al-majlis necessitates the physical presence of all parties in one location during the marriage contract process, whereas proponents contend that the virtual realm fulfills this criterion. These findings reflect the ongoing societal dialogue regarding the interpretation of religious doctrines and technological innovations, offering valuable insights into the intersection of religious tradition and technology in contemporary Islamic jurisprudence. [Studi ini menginvestigasi perspektif para penghulu di Kota Banjarmasin terkait hukum akad nikah secara online, yang mencerminkan pergumulan antara tradisi keagamaan dan kemajuan teknologi. Dengan mengacu pada perbedaan pendapat para ulama fikih tradisional, artikel ini mengidentifikasi perbedaan dalam penafsiran terhadap ittiḥād al-majlis sebagai salah satu syarat ijab dan kabul dalam perkawinan, yang mempengaruhi pendapat para penghulu tentang sah tidaknya akad nikah secara online. Di tengah kompleksitas ini, artikel bertujuan untuk menganalisis faktor-faktor yang membentuk perdebatan para penghulu terkait hukum akad nikah secara online serta implikasinya dalam konteks masyarakat Banjar. Dengan mewawancarai 12 penghulu di Kota Banjarmasin selama tiga bulan, dari September sampai November 2023, studi ini menyoroti pentingnya tradisi keagamaan dalam masyarakat Banjar dan adaptasi terhadap perkembangan teknologi dalam penafsiran terhadap hukum Islam. Kajian ini menunjukkan bahwa mayoritas penghulu menolak akad nikah secara online, sementara sebagian kecil memperbolehkannya dengan syarat tertentu. Mayoritas penghulu yang menolak menginterpretasikan ittiḥād al-majlis dengan keharusan kehadiran para pihak secara fisik dalam satu tempat dalam prosesi akad nikah, sedangkan sebagian kecil yang membolehkan memandang bahwa ruang virtual telah memenuhi kriteria ittiḥād al-majlis tersebut. Temuan ini mencerminkan perdebatan yang sedang berlangsung dalam masyarakat terkait penafsiran terhadap ajaran agama dan perkembangan teknologi, memberikan wawasan yang berharga tentang dinamika tradisi keagamaan dan teknologi dalam pemikiran hukum Islam kontemporer.]